Molecular screening for vel- blood donors in Southwestern Germany - Wieckhusen, Carola; Bugert, Peter (Transfusion medicine and hemotherapy, 2015)
Background: The SMIM1 protein carries the Vel blood group antigen, and homozygosity for a 17 bp deletion in the coding region of the SMIM1 gene represents the molecular basis of the Vel- blood group phenotype. We developed PCR-based methods for typing the SMIM1 17 bp (64-80del) gene deletion and performed a molecular screening for the Vel- blood type in German blood donors. Methods: For SMIM1 genotyping, TaqMan-PCR and PCR-SSP methods were developed and validated using reference samples. Both methods were used for screening of donors with blood group O from southwestern Germany. Heterozygotes and homozygotes for the SMIM1 64-80del allele were serologically typed for the Vel blood group antigen. In addition, the rs1175550 SNP in SMIM1 was typed and correlated to the results of the phenotyping. Results: Both genotyping methods, TaqMan-PCR and PCR-SSP, represent reliable methods for the detection of the SMIM1 64-80del allele. Screening of 10,598 blood group O donors revealed 5 individuals homozygous for the deletional allele. They were confirmed Vel- by serological typing. Heterozygotes for the 64-80del allele showed different antigen expressions ranging from very weak to regular positive. Conclusion: Molecular screening of blood donors for the Vel- blood type is feasible and avoids the limitations of serological typing which might show false-negative results with heterozygous individuals. The identification of Vel- blood donors significantly contributes to the adequate blood supply of patients with anti-Vel.